Development of an Anxiety Management Package for Mothers with Children Preparing for University Entrance Exams - Mirzaei, Morteza; Yousefi, Zahra; Baratali, Maryam (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aimed to develop an anxiety reduction package for mothers with children preparing for university entrance exams. Methodology: This research was qualitative in nature. In the first section, an exploration of the anxiety experienced by mothers with children preparing for university entrance exams was conducted using the thematic analysis method by Clarke and Braun (2006). In the second section, the anxiety management package was developed using the package development method by Yousefi and Golparvar (2023). The study population consisted of all mothers with children preparing for university entrance exams in the city of Shiraz during the 2022-2023 academic year. Participants were selected using purposive sampling, and the number of participants was determined based on the principle of data saturation, resulting in ten participants. Data were collected through semi-structured interviews. Findings: The results of the interview analysis using the six-step method by Clarke and Braun (2019) indicated that the anxiety experienced by these mothers included two overarching categories: anxiety for the child (with organizing categories of outcome-related anxiety, competition-related anxiety, and process-related anxiety) and anxiety related to maternal performance (with organizing categories of maternal performance anxiety related to the entrance exam and anxiety regarding the inability to control the child). In the package development section, the hidden goal of this package was to reduce mothers' anxiety to enhance their children's academic performance through awareness and skill-building to manage maternal anxiety using positive psychology strategies (Frisch, 2006). This was achieved using the package development method by Yousefi and Golparvar (2023), where selected strategies from positive psychology were aligned with the extracted categories. The results of this integration led to an eight-session educational package, with objectives focused on reducing maternal anxiety and strategies derived from positive psychology. Finally, the educational package was validated through content validity evaluation by experts using the assessors' agreement coefficient, and the results indicated content validity. Conclusion: Based on these findings, it can be concluded that this package is appropriate for managing anxiety in mothers of children preparing for university entrance exams.